2016
DOI: 10.1080/23322373.2016.1175266
|View full text |Cite
|
Sign up to set email alerts
|

African Smart Cities Strategies for Agenda 2063

Abstract: By synthesizing urbanization challenges and current trends in Africa, this dialogue piece captures the broader transformative processes taking place on the continent. We develop a vision of the African cities of the future and show the alignment of key aspects of the 'smart city' concept with the African Union's Agenda 2063. Looking at the approximately 50-year time horizon of Agenda 2063 (at the time of writing, 2016), we chart the strategy space for African megacities, medium cities, as well as small cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 27 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…Figures 6-9 show the modernist architectural language adopted by Smart Cities to support a heavy branding by competing companies. These new Smart City towns are part of the long history of New Towns created as part of the modernist tradition [64]. This tradition, with its roots in Le Corbusier's Congrès Internationaux d'Architecture Moderne (CIAM) movement, aimed to start from a clean slate and use modern high rise and freeway architecture to create a new kind of urban experience.…”
Section: Dichotomy Between Bringing Smart Technology To Old Cities Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 6-9 show the modernist architectural language adopted by Smart Cities to support a heavy branding by competing companies. These new Smart City towns are part of the long history of New Towns created as part of the modernist tradition [64]. This tradition, with its roots in Le Corbusier's Congrès Internationaux d'Architecture Moderne (CIAM) movement, aimed to start from a clean slate and use modern high rise and freeway architecture to create a new kind of urban experience.…”
Section: Dichotomy Between Bringing Smart Technology To Old Cities Ormentioning
confidence: 99%
“…These values provide a focus for the Smart City to address the issues of urbanization [16,18,19] and to welcome urbanization as an essential condition for growth [71]. These values also allow policy-makers to distinguish between different types of cities and different urban fabrics and to highlight the need for different developmental agendas [57,64]. This approach is far from the "one-size fits all, modernist model presented by Smart City suppliers, suggesting that smart infrastructure, as an isolated item, places an additional financial burden on the city's governing bodies despite most cities struggling to find finance for their multiple socio-economic problems [65].…”
Section: Creating a Smart City Frameworkmentioning
confidence: 99%
“…Slavova and Okwechime [82] examined the broader transformative processes taking place in Africa and developed a vision of the future African cities. The authors showed the alignment of critical aspects of the smart city concept with the African Union's Agenda 2063.…”
Section: South Africamentioning
confidence: 99%
“…Several African and South American cities have also started to work towards designing smart and modern transportation systems [98,99]. The Benin City transportation systems were upgraded with an advanced ITS system that assesses traffic flow in real time [100].…”
Section: Smart Transportation Approaches Advances and Applicationsmentioning
confidence: 99%
“…The previous studies on the ensuring of public involvement are not reliable [58][59][60][61][62][63][64][65][66][67][68][69]. Despite the emerging recognition that an organized involvement of stakeholders should become central to all the relevant features of smart transportation studies [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], limited attention has been paid to encouraging different stakeholders in all critical stages of smart city agendas [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Furthermore, visions are composed of several vital drivers and not all the key drivers are of similar desirability [115] and reflecting nuances of value-laden perspectives by separating different clusters of desirability makes i...…”
Section: Smart Transportation Approaches Advances and Applicationsmentioning
confidence: 99%